2021
DOI: 10.1210/jendso/bvab048.1864
|View full text |Cite
|
Sign up to set email alerts
|

A Grave Initial Presentation of Graves’ Disease in a Patient With Moyamoya

Abstract: Background: Moyamoya syndrome is chronic stenoocclusive disease involving the intracranial internal carotid arteries and their proximal branches along with an associated condition, such as hyperthyroidism1. The concurrence of moyamoya and Graves’ disease is rare. Ischemic stroke in moyamoya syndrome is postulated to be precipitated by thyrotoxicosis-induced hemodynamic instability. Clinical Case: A 63-year old Korean female with history of moyamoya disease with two prior ischemic strokes, hypertension and type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Revascularization is the main treatment for MMD patients. Previous studies have shown that revascularization benefited most MMD patients including ischemic [ 12 , 13 ] and hemorrhagic types [ 14 16 ]. While revascularization is disadvantage for some patients because of postoperative complications associated with the disturbance of cerebral hemodynamics [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Revascularization is the main treatment for MMD patients. Previous studies have shown that revascularization benefited most MMD patients including ischemic [ 12 , 13 ] and hemorrhagic types [ 14 16 ]. While revascularization is disadvantage for some patients because of postoperative complications associated with the disturbance of cerebral hemodynamics [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%